2007
DOI: 10.1038/sj.onc.1210239
|View full text |Cite
|
Sign up to set email alerts
|

Differential oncogenic potential of activated RAS isoforms in melanocytes

Abstract: RAS genes are mutated in approximately 30% of all human cancers. Interestingly, there exists a strong bias in favor of mutation of only one of the three major RAS genes in tumors of different cellular origins. NRAS mutations occur in approximately 20% of human melanomas, whereas HRAS and KRAS mutations are rare in this disease. To define the mechanism(s) responsible for this preference in melanocytes, we compared the transformation efficiencies of mutant NRAS and KRAS in immortal, non-transformed Ink4a/Arf-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 28 publications
2
59
0
2
Order By: Relevance
“…For mutant KRAS, the expression of a cooperating oncogene was necessary to reach a comparable transforming capacity, as mutant NRAS in a genetically welldefined system using NRAS and KRAS transformed melanocytes. 21 Thus, the simultaneous occurrence of c-Kit and a KRAS mutation may reflect such a cooperating oncogenic activity in a subset of esophageal melanomas. Interestingly, we could not confirm the results of a Japanese study, which showed a frequent occurrence of NRAS mutations in esophageal melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…For mutant KRAS, the expression of a cooperating oncogene was necessary to reach a comparable transforming capacity, as mutant NRAS in a genetically welldefined system using NRAS and KRAS transformed melanocytes. 21 Thus, the simultaneous occurrence of c-Kit and a KRAS mutation may reflect such a cooperating oncogenic activity in a subset of esophageal melanomas. Interestingly, we could not confirm the results of a Japanese study, which showed a frequent occurrence of NRAS mutations in esophageal melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NRAS mediates activation of both MAPK and PI3K/AKT/MYC signaling. Specifically, although both NRAS and KRAS efficiently activate the classical MAPK pathway, only NRAS effectively prevents glycogen synthase kinase3 (GSK3)-mediated phosphorylation of Myc via PI3K/AKT, which results in enhanced activity of endogenous Myc protein [37]. In contrast to KRAS, NRAS and HRAS also show a more potent activation of PI3K/AKT likely due to the fact that both NRAS and HRAS colocalize to lipid rafts, whereas KRAS is excluded from lipid rafts and localizes to the disordered plasma membrane [38], resulting in a less efficient activation or a limited access to a defined subset of downstream effector proteins.…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 99%
“…A rational explanation for the greater occurrence of NRAS mutations relies on distinct differences between the signaling capabilities of NRAS and KRAS in melanocytes [37]. When the transformation efficiencies of mutant NRAS and KRAS were compared in immortal, non-transformed Ink4a/Arf-deficient melanocytes, it was shown that in contrast to KRAS mutation, NRAS mutation leads to increased cellular proliferation and is more potently tumorigenic [37]. Furthermore, NRAS mediates activation of both MAPK and PI3K/AKT/MYC signaling.…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 99%
“…The aberration of NRAS often is a substitution of leucine for glutamine at residue 61, this change impairs GTP hydrolysis and maintains the protein in a state of constitutive activation (41). Mutations in other Ras isoforms are rare in melanoma, suggesting an activity context dependent on specific Ras isoforms (42).…”
Section: Abnormal Activation Of the Map Kinase Cascade In Melanomamentioning
confidence: 99%